VARIANT OF A NOT HIPERBOLIC SYSTEMS - Sulca Paredes, Teodoro (2012)
Already in the article [5] we consider the not hiperbolic system which is transformed inand analyze the case when k is an odd number. In the present article will analyzethe behaviour of the trajectories in the vicinity of a isolated singular point , when kis a number pair.